2007
DOI: 10.1037/0002-9432.77.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Homophobia and conservative religion: Toward a more nuanced understanding.

Abstract: The failure of homophobia scales to consider the normative assumptions of religious communities may result in findings that are less useful in addressing this problem. In this study, 155 undergraduate students at a Christian university were surveyed, separately assessing attitudes toward celibate versus sexually active homosexual men and women. Results of multiple regression analyses found that participants who emphasized a person-behavior distinction (an accepted tenet of conservative religious ideology) held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 48 publications
(69 reference statements)
3
32
0
1
Order By: Relevance
“…The study found a strong correlation between religious fundamentalism and these attitudes. Similar to other studies (Rosik, Griffith, & Cruz, 2007;Wolff et al, 2012), there was little gender difference in student perceptions of homosexuality.…”
Section: Perceptions Of Heterosexual Studentssupporting
confidence: 68%
See 3 more Smart Citations
“…The study found a strong correlation between religious fundamentalism and these attitudes. Similar to other studies (Rosik, Griffith, & Cruz, 2007;Wolff et al, 2012), there was little gender difference in student perceptions of homosexuality.…”
Section: Perceptions Of Heterosexual Studentssupporting
confidence: 68%
“…Universities affiliated with such denominations are likely to reflect similar values (Wentz & Wessel, 2011). Results from the Rosik et al (2007) study confirm that sexual behavior is more relevant than sexual orientation, with some students capable of making "a meaningful distinction between the value of homosexual persons and the value of their sexual behavior" (p.16). Students at religious universities who experience SSA also make a distinction between identity and behavior.…”
Section: Person-behavior Distinctionsupporting
confidence: 66%
See 2 more Smart Citations
“…A. Wilson, Wittlin, MunozLaboy, & Parker, 2011). Religions with punitive, fundamentalist doctrines are associated with increased homophobia (Balkin, Schlosser, & Levitt, 2009;Rosik, Griffith, & Cruz, 2007;Miller, 2007;Ward, 2005). There are at least three separate studies reporting that MSM's exposure to these types of religious environments have been associated with development of internalized homophobia (Barnes & Meyer, 2012;Pitt, 2009;Wilkerson, Smolenski, Brady, & Rosser, 2012).…”
mentioning
confidence: 99%